Assessment of acid soils for sanitary landfill in Khana Local Government Area of Rivers State, South – South, Nigeria - Kaananwii Dum Peter; Vincent Mmbue Nwidae (Ilmu Pertanian (Agricultural Science))
Open dumping of refuse is the order of the day and the collective method for discarding municipal solid waste, and the inefficient way of handling waste coupled with poor planning of landfill has resulted to environmental pollution and land degradation. Sanitary landfills are therefore necessary for the appropriate disposal of municipal waste. Thus, this study was carried out to assess the soils of Beeri in Khana Local Government Area for sanitary landfill. Three soil map units (pedons) based on vegetation, toposequence and drainage were identified and delineated in the study area. A modal soil profile of 2 m × 2 m × 2 m dimensions was dug in the identified soil map units, and the genetic horizons were labeled and sampled for laboratory analysis. Results obtained revealed that sand fractions varied from 804 g/kg in horizon-B of pedon 2 to 924 g/kg in pedon 1; silt content varied between 14 g/kg in horizon-AB of pedon 3 to 24 g/kg in B-horizon of pedons 1 and 2; and clay content decreased from 172 g/kg in B-horizon of pedon 2 to 52 g/kg in pedon 1. Bulk density decreased from 0.935 gcm⁻³ in horizon-Ah of pedon 1 to 1.4550 gcm⁻³ in B-horizon of pedon 2. Soil pH ranged from strongly acidic 4.89 in AB-horizon of pedon 2 to slightly acidic 5.47 in Bw-horizon of pedon 1. Effective cation exchange capacity decreased from10.86 cmolkg⁻¹ in pedon 2 to 2.84 cmol/kg in pedon 3. Soil suitability assessment of the study area indicated that the soils were not suitable (N) for the construction and operation of sanitary landfill as a result of defects in soil texture, high sand and low clay contents, porosity, and low ECEC. Therefore, it is necessary to make efforts to improve texture, bulk density, porosity, and ECEC through appropriate management practices so that the physical and chemical properties of the soil can be improved to a moderate to high level of suitability for sanitary landfill.